2016
DOI: 10.2119/molmed.2016.00054
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide induces Neutrophil Extracellular Trap Formation in a TLR-4 and NOX-Dependent Mechanism

Abstract: Neutrophils constitute the early innate immune response to perceived infectious and sterile threats. Neutrophil extracellular traps (NETs) are a novel mechanism to counter pathogenic invasion and sequelae of ischemia, including cell death and oxidative stress. Superoxide is a radical intermediate of oxygen metabolism produced by parenchymal and nonparenchymal hepatic cells, and is a hallmark of oxidative stress after liver ischemia-reperfusion (I/R). While extracellular superoxide recruits neutrophils to the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(62 citation statements)
references
References 53 publications
(52 reference statements)
2
53
0
Order By: Relevance
“…14,15,26,29 NETosis was initially thought to be merely another facet of this antimicrobial role, as NETs are released in response to bacterialdependent Toll-like Receptor (TLR) or immunoglobulin-dependent Fc receptor activation. 17,30,31 However, NETs have since been shown to form under various sterile inflammatory conditions, including autoimmune disease, 32 crystallopathy, 22 and organ injury. 20,21,33 In sterile inflammation, NETs enhance the pro-inflammatory response through the cytotoxicity of free histones, 34 transformation of pro-IL-1β into active IL-1β by NET-based enzymes, 35 and direct action as a DAMP signal for other immune cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,15,26,29 NETosis was initially thought to be merely another facet of this antimicrobial role, as NETs are released in response to bacterialdependent Toll-like Receptor (TLR) or immunoglobulin-dependent Fc receptor activation. 17,30,31 However, NETs have since been shown to form under various sterile inflammatory conditions, including autoimmune disease, 32 crystallopathy, 22 and organ injury. 20,21,33 In sterile inflammation, NETs enhance the pro-inflammatory response through the cytotoxicity of free histones, 34 transformation of pro-IL-1β into active IL-1β by NET-based enzymes, 35 and direct action as a DAMP signal for other immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…13,15,16 Neutrophil activation is often triggered by pathogen-associated molecular patterns (PAMPs) binding to toll-like receptor-4 (TLR-4) during non-sterile inflammation. 17 These events have been long understood to serve antimicrobial purposes: propagate the immune response, limit pathogen activity, and enhance clearance of bacteria. However, recent studies have shown a role for neutrophils-namely, NETosisin sterile inflammation, which may be triggered by release of danger-associated molecular patterns (DAMPs).…”
Section: Introductionmentioning
confidence: 99%
“…At present, the most studied model is suicidal netosis, which lasts for 2-4 hours. Its onset is characterized by neutrophil activation, through the recognition of pathogens, which leads to the induction of the NADPH oxidase (NOX) complex, through protein kinase C, and to an increase in cytosolic Ca + [21][22][23]. These cations serve as a co-factor for peptidyl-arginase deaminase 4 (PAD4) and a nuclear enzyme that deaminates histones, modifies amino acids, which leads to decondensation of chromatin and loss of positive charges necessary for the interaction of histones with DNA [24,25].…”
Section: B B1mentioning
confidence: 99%
“…NETosis in LDGs is at least in part dependent on mitochondrial ROS production, as treatment with the mitochondrial ROS scavenger MitoTempo significantly abrogates the extrusion of NET structures in these cells [51]. Neutrophils exposed to extracellular superoxide also display enhanced NET formation and this is associated with concomitant liver injury [72]. Of consequence, the study by Lood et el.…”
Section: Role Of Ros In Tissue Damage and Immune Cell Activation In Lmentioning
confidence: 99%